Left ventricular function in mitral valve prolapse and severe mitral regurgitation - E. G. Malev; G. I. Kim; L. B. Mitrofanova; M. Yu. Omelchenko; E. V. Zemtsovsky (Российский кардиологический журнал, 2013)
Aim. To assess systolic left ventricular (LV) function in patients with mitral valve prolapse (MVP) and different morphological MV disorders. Material and methods. The study included 233 patients (mean age 53,8±12,9 years), who underwent MV surgery due to MPV and severe mitral regurgitation (MR) at the V. A. Almazov Federal Centre of Heart, Blood, and Endocrinology in 2009-2011. The resected MV segments underwent a pathomorphological examination; preoperative strain and strain rate were assessed with the speckle tracking method (EchoPAC’08). Results. Based on the pathomorphological data, Barlow’s disease was registered in 60 patients (25,8%), and fibroelastic deficiency in 173 patients (74,2%). The preintervention echocardiography did not demonstrate any significant difference between the two groups in terms of preoperative MR volume (70,5±9,6 ml vs. 71,6±8,5 ml, p=0,40), systolic LV function (ejection fraction 52,7±6,6% vs. 52,0±7,4%; p=0,53) and diastolicLV function (E/e’ 12,2±3,9 vs. 12,8±4,2; p=0,35). Despite no difference in ejection fraction, the Barlow’s disease group demonstrated a significant reduction inLV longitudinal systolic (-13,5±2,2% vs. -16,6±2,3%; p=0,008) and diastolic strain (1,14±0,20 s-1 vs. 1,34±0,18 s-1; p=0,04), as well as in strain rate (-0.89±0,15 s-1 vs. -1,14±0,15 s-1; p=0,002), compared to the fibroelastic deficiency group. Conclusion. Patients with Barlow’s disease, compared to patients with fibroelastic deficiency, have a lower preoperative LV systolic function, which might affect the postoperative long-term survival rates. The deteriorated LV function could be due to the damage of endocardial and intramyocardial extracellular matrix in Barlow’s disease.